2019
DOI: 10.3892/mmr.2019.10319
|View full text |Cite
|
Sign up to set email alerts
|

p53 mediates PEDF‑induced autophagy in human umbilical vein endothelial cells through sestrin2 signaling

Abstract: Autophagy is a conserved catabolic process by which cytoplasmic components are delivered into lysosomes for degradation. Pigment epithelium-derived factor (PEDF) has been reported to be associated with autophagy and can induce p53 expression; however, the mechanism relating PEDF with autophagy in endothelial cells remains poorly understood. The present study aimed to investigate the association between the PEDF-p53-sestrin pathway and autophagy in human umbilical vein endothelial cells (HUVECs). PEDF-induced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Pigment epithelium-derived factor (PEDF) could inhibit mTORC1 and induce autophagy in human umbilical vein endothelial cells by activating the P53/Sestrin2 signaling pathway. Silencing P53 or Sestrin2 abrogated the effect of PEDF on endothelial cell autophagy [27]. PEDF also suppressed the inflammatory response of macrophages and stabilized atherosclerotic plaques [28].…”
Section: Sestrin2 In Cardiovascular Diseasesmentioning
confidence: 94%
“…Pigment epithelium-derived factor (PEDF) could inhibit mTORC1 and induce autophagy in human umbilical vein endothelial cells by activating the P53/Sestrin2 signaling pathway. Silencing P53 or Sestrin2 abrogated the effect of PEDF on endothelial cell autophagy [27]. PEDF also suppressed the inflammatory response of macrophages and stabilized atherosclerotic plaques [28].…”
Section: Sestrin2 In Cardiovascular Diseasesmentioning
confidence: 94%
“…Studies have shown that the knockout of Sesn2 can induce endothelial dysfunction through AMPK dependent pathway and accelerate the formation of LPS induced-myocardial fibrosis ( 111 ), while the over-expression of Sesn2 can activate AMPK to alleviate sepsis induced-myocardial dysfunction ( 112 ). In the umbilical vein endothelial cells, pigment epithelium derived factor (PEDF) induces the expression of p53 and Sesn2, and inhibits mTOR, so as to trigger autophagy ( 113 , 114 ). Other studies have shown that over-expression of Sesn2 triggers mitochondrial autophagy, enhances mitochondrial function, and improves myocardial dysfunction induced by doxorubicin ( 115 ).…”
Section: Role Of Cascade Autophagy In Cardiovascular Disease Through ...mentioning
confidence: 99%
“…A variety of adverse stresses could promote Sestrin2 expression, such as oxidative stress, ER stress, hypoxia, energetic stress, and age-and obesity-associated metabolic pathological conditions (7)(8)(9)(10). Up-regulated Sestrin2 exerts pleiotropic biological effects in diverse physiological and pathological states, through attenuating oxidative stress, and modulating a series of cellular events such as autophagy, ER stress, mitochondrial biogenesis, protein synthesis, cell energy homeostasis and apoptosis, while many of these responsive pathways are interconnected (5,(11)(12)(13)(14).…”
Section: Sestrinpathways and Modulating Mechanismsmentioning
confidence: 99%